Purification and Characterization of Karadi Sheep Milk Proteins - Jasim M. S. Al-Saadi (Journal of Global Pharma Technology, 2018)
The distribution of nitrogen in Karadi sheep milk showed protein nitrogen to be 94.6% of the total nitrogen, non-protein nitrogen 5.4%, casein nitrogen 72.9% and whey nitrogen protein 21.7%. β-Lacto globulin (β-Lg), α-lactalbumin (α-La), κ-casein (CN), αs-CN and β-CN were purified from sheep milk using gel filtration and ion-exchange chromatography. The molecular weights of the purified α-La, β-La, κ-CN, β-CN and αs-CN were 14.01, 18.05, 21.3, 24.8 and 24.95 kDa, respectively. Phosphorus levels in κ-CN, β-CN and αs-CN were 3.14, 7.84 and 11.75 mg/g protein respectively. Κ-CN contained 49.1 mg carbohydrates/g protein.Keywords: Sheep milk, Protein purification, Chromatography, Caseins, Whey proteins.